THE EFFECT OF PLEASE STRATEGY ON THE ABILITY OF THE FIRST YEAR STUDENTS OF SMP N 5 PEKANBARU IN PARAGRAPH WRITING - Siringoringo, Artarty; Aruan, Rumiri; Sumbayak, Desri Maria (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was aimed to finding out the effect of PLEASE strategy on the ability of the first year students of SMP N 5 Pekanbaru in paragraph writing. This study was a pre experimental research with one group pre-test and post-test design. A single group was chosen to be the sample of this study by cluster random sampling to get six treatments. There were 36 students joined this study as experimental group. A writing test was used both in pre and post-test. In order to know the difference between pre and post-test and to analyze the hypotheses, t-test formula by Hatch and Farhady (1982) was used. After analyzing the data, it was found out that t-test score was 19.50 while t-table was 2.03 with the level of significant 5% and 2.72 with the level of significance 1%. Since t-test was higher than t-table, it can be concluded that alternative hypothesis was accepted and there was a significant effect of PLEASE strategy on the ability of the first year students of SMP N 5 Pekanbaru in paragraph writing.Keywords: PLEASE strategy, writing ability, junior high school students